Pengaruh Pemberian Beberapa Konsentrasi Pupuk Organik Cair (Poc) Bonggol Pisang Terhadap Pertumbuhan Dan Hasil Tanaman Kacang Kedelai (Glycine max L.) - Veronica, Nabila; Sevindrajuta, Sevindrajuta; Amir, Yusnaweti (CULTIVATE: Journal of Agriculture Science, 2026)
This research, entitled “The Effect of Several Concentrations of Banana Corm Liquid Organic Fertilizer (LOF) on the Growth and Yield of Soybean Plants (Glycine max L.)”, was carried out at the experimental field of the Faculty of Agriculture, Muhammadiyah University of West Sumatra, from August 2024 to November 2024. The aim of this study was to determine the best concentration of banana corm LOF application on the growth and yield of soybean plants. The research used a Randomized Block Design (RBD) with 5 treatments and 4 groups, resulting in 20 experimental plots. Each plot contained 16 plants, with 3 plants used as samples. The treatments consisted of applying banana corm LOF concentrations of 0 ml/liter of water, 20 ml/liter of water, 40 ml/liter of water, 60 ml/liter of water, and 80 ml/liter of water. The observational data were averaged and statistically analyzed using the F-test at a 5% significance level, followed by Duncan’s New Multiple Range Test (DNMRT) at the same significance level.The observed parameters included plant height, number of pods per plant, seed weight per plant, seed weight per plot, seed weight per hectare, and the weight of 100 soybean seeds. The results of the study concluded that the application of 80 ml/liter of banana corm LOF was able to improve the growth and yield of soybean plants.